EVALUATION OF ORAL HEALTH STATUS IN CHILDREN WITH AUTISM - Faazila Fathima; Mebin George Mathew; SenthilMurugan P (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Autism spectrum disorder is one of the most severe childhood neuropsychiatric conditions. Autistic individuals are characterized by impairment in social interaction with a restricted range of interests and repetitive behaviors.The population with autism spectrum disorders presents with similar health problems as that of the normal individuals, but due to factors like poor dietary preferences, behaviors and specific aversions, autistic patients are at a greater risk and are more susceptible to developing chronic non-communicable oral health conditions.The increasing prevalence of autism spectrum disorder has brought an interest in their oral health concerns, which coincides with one of the global oral health goals to promote oral health within this population.The aim of this study is to evaluate the oral health status in children with autism.Records of pediatric patients who reported to Saveetha Dental College and Hospitals from June 2019 to March 2020 were reviewed. 16 pedodontic patients who had autism were included in this study. Clinical examination, dental status and photographs of these patients were evaluated.The oral health status of autistic children were evaluated using DMFT and OHIS index.The data was entered in IBM SPSS 20.0 software and analyzed using Chi square test. From the results of this study, it was observed that OHI score of 1 or less(69%) and DMFT score of 2 or below(63%) was most prevalent among the study population of autistic children. Higher DMFT and OHI score was more commonly observed in 11 to 15 years of age and males showed more prevalence of poor oral health than females.Within the limitations of the current study, it can be concluded that children with autism exhibited poor oral health status.